Association of Epstein-Barr Virus with Gastric Carcinoma among Sudanese Patients - omer, Ibtihal; salahddin, Dalia; Hussein Musa, Hassan; Ahmed, Mona; abdalrahman, Hosham (Journal of Cancer Genetics And Biomarkers, 2016)
Background: Gastric cancer (GC) ranks as the fourth most common cancer and the second leading cause of cancer deaths worldwide. Epstein-Barr virus is a well-known oncogenic virus, it is responsible for 10% of gastric carcinomas across the world. The aim of study was to determine the prevalence of EBV associated with GC in Sudanese patients. Method: Fifty Paraffin embedded blocks of gastric biopsy specimens diagnosed as gastric carcinoma were collected from Soba university hospital and Ribat teaching hospital, Khartoum, Sudan. DNA was extracted from the paraffin-embedded tissue, and then Epstein-Barr virus gene was detected by polymerase chain reaction (PCR). Result: Among the gastric biopsy specimens 27 (54.0%) were of male and 23(46.0%) were of female. Eleven EBV positive samples were found in gastric carcinomas (22.0%), 8 (72.7%) were of male and 3(27.2%) were of female. The mean age of the patients was 56 years, the most positive cases were between 50-59 years old, and (10%) of them are alive in Khartoum. Conclusions: There exists an association between EBV and gastric carcinoma in some Sudanese patients.
Keywords: Epstein-Barr virus; PCR; Gastric carcinoma; Sudan; Africa